Avaliação da qualidade de vida relacionada à saúde bucal e visita ao dentista em pré-escolares - Perazzo, Matheus de França (2016)
OBJECTIVE: Evaluate oral health-related quality of life (OHRQoL) and visits to the dentist among five-year-old preschool children. METHODS: A school-based cross- sectional study was conducted with 769 pairs of parents/caregivers and children enrolled at public and private schools in the city of Campina Grande in northeast Brazil. Socio-demographic characteristics of the families and information on seeking dental services for the children were determined using a questionnaire administered to parents/caregivers. The children and parents/caregivers answered the respective versions of the Scale of Oral Health Outcomes for Five-Year-Old Children (SOHO-5). Parents/caregivers then answered the short version of the Sense of Coherence scale (SOC-13). Clinical examinations were performed by two examiners who had previously undergone a training exercise (inter-examiner Kappa: 0.80-1.00; intra- examiner Kappa: 0.82-1.00) for the evaluation of dental caries, traumatic dental injury and malocclusion. Sleep bruxism was determined based on the reports of parents/caregivers. Descriptive analysis was performed, followed by Poisson regression analysis (α = 5%). RESULTS: The children had higher total SOHO-5 scores than their parents/caregivers (2.37 ± 3.35 and 1.08 ± 2.65, respectively). The following variables were significantly associated with impact on the children‟s OHRQoL in the parent/caregiver version: public preschool (PR = 1.68; 95% CI: 1.32- 2.13), history of toothache (PR = 4.26; 95% CI: 2.86-6.32), cavitated lesions on anterior teeth (PR = 2.68; 95% CI: 1.02-2.75) and the consequences of untreated dental caries (PR = 2.25; 95% CI: 1.51-3.36). The following variables were significantly associated with impact on the child self-report version: public preschool (PR = 1.27; 95% CI: 1.01-1.86), history of toothache (PR = 1.59; 95% CI: 1.26-2.00), white spot on anterior teeth (PR = 1.75; 95% CI: 1.24-2.46), cavitated lesions on anterior teeth (PR = 1.68; 95% CI: 1.24-2.75), occurrence of traumatic dental injury (PR = 1.27; 95% CI: 1.02-1.58) and anterior open bite (PR = 1.39; 95% CI: 1.01- 1.92). A total of 43.5% of the preschool children had visited a dentist at least once in their lifetimes. The following variables were significantly associated with a history of visits to the dentist: higher household income (PR = 1.27; 95% CI: 1.07-1.51), history of toothache (PR = 1.59; 95% CI: 1.34-1.89), absence of traumatic dental injury (PR = 1.18; 95% CI: 1.01-1.40) and a strong sense of coherence on the part of parents/caregivers (PR = 1.19; 95% CI: 1.01-1.42). CONCLUSION: For both the child and parent/caregiver subscales of the SOHO-5, a greater difference in mean OHRQoL scores was found among children who attended public preschools as well as those with dental caries experience and experience with the consequences of dental caries. Moreover, the aesthetic component exerted a greater impact on OHRQoL in the children‟s self-reports. Visits to the dentist were associated with a higher socioeconomic status, a history of toothache, an absence of traumatic dental injury and a strong sense of coherence among parents/caregivers.